Body Temperature after EMS Transport: Association with Traumatic Brain Injury Outcomes. (3rd September 2017) - Gaither, Joshua B.; Chikani, Vatsal; Stolz, Uwe; Viscusi, Chad; Denninghoff, Kurt; Barnhart, Bruce; Mullins, Terry; Rice, Amber D.; Mhayamaguru, Moses; Smith, Jennifer J.; Keim, Samuel M.; Bobrow, Bentley J.; et al.
Abstract: Introduction : Low body temperatures following prehospital transport are associated with poor outcomes in patients with traumatic brain injury (TBI). However, a minimal amount is known about potential associations across a range of temperatures obtained immediately after prehospital transport. Furthermore, a minimal amount is known about the influence of body temperature on non-mortality outcomes. The purpose of this study was to assess the correlation between temperatures obtained immediately following prehospital transport and TBI outcomes across the entire range of temperatures.Methods : This retrospective observational study included all moderate/severe TBI cases (CDC Barell Matrix Type 1) in the pre-implementation cohort of the Excellence in Prehospital Injury Care (EPIC) TBI Study (NIH/NINDS: 1R01NS071049). Cases were compared across four cohorts of initial trauma center temperature (ITCT): <35.0°C [Very Low Temperature (VLT)]; 35.0–35.9°C [Low Temperature (LT)]; 36.0–37.9°C [Normal Temperature (NT)]; and ≥38.0°C [Elevated Temperature (ET)]. Multivariable analysis was performed adjusting for injury severity score, age, sex, race, ethnicity, blunt/penetrating trauma, and payment source. Adjusted odds ratios (aORs) with 95% confidence intervals (CI) for mortality were calculated. To evaluate non-mortality outcomes, deaths were excluded and the adjusted median increase in hospital length of stay (LOS), ICU LOS and total hospital charges were calculated for each ITCT group and compared to the NT group.Results : 22, 925 cases were identified and cases with interfacility transfer (7361, 32%), no EMS transport (1213, 5%), missing ITCT (2083, 9%), or missing demographic data (391, 2%) were excluded. Within this study cohort the aORs for death (compared to the NT group) were 2.41 (CI: 1.83–3.17) for VLT, 1.62 (CI: 1.37–1.93) for LT, and 1.86 (CI: 1.52–3.00) for ET. Similarly, trauma center (TC) LOS, ICU LOS, and total TC charges increased in all temperature groups when compared to NT.Conclusion : In this large, statewide study of major TBI, both ETs and LTs immediately following prehospital transport were independently associated with higher mortality and with increased TC LOS, ICU LOS, and total TC charges. Further study is needed to identify the causes of abnormal body temperature during the prehospital interval and if in-field measures to prevent temperature variations might improve outcomes.